Zur Kenntnis der Populationsdynamik und des Migrationsverhaltens von Vanessa atalanta L. im paläarktischen Raum (Lepidoptera). - Warnecke, G.; Harz, Kurt (Contributions to Entomology = Beiträge zur Entomologie, 1964)
There is given a critical contribution to the paper of H. Roer (Beitr. Ent., 11, 594-613; 1961). The conclusion of H. Roer that Vanessa atalanta L. would hibernate in Central Europe and therefore would be indigenous is considered as false conclusion by insufficient statements and facts and incorrect suppositions.